Keefektifan Pembelajaran Menulis Karya Ilmiah Dengan Model Berbasis Masalah Berdasarkan Tingkat Berpikir Kreatif Mahasiswa - Gusnayetti (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Writing scientific papers is one of the lessons in higher education. Scientific work is a piece of writing or composition written by an individual or group that discusses objective facts presented in accordance with good and correct writing methodology and uses scientific language. In this research the model used is a problem-based model. In addition, it is necessary to moderator variable, namely the level of creative thinking. This research aims to (1) analyze the effectiveness of learning to write scientific papers using a problem-based model based on students' level of creative thinking; (2) analyze the effectiveness of learning to write scientific papers using a problem-based model based on the level of creative thinking in students.